Location of the mandibular foramen according to the amount of dental alveoli - Valente, Vitor Bonetti; Arita, Welton Massato; Garcia Goncalves, Pedro Cesar; Duarte Bonini Campos, Juliana Alvares; Capote, Ticiana Sidorenko de Oliveira [UNESP] (Soc Chilena Anatomia, 2012)
The aim of this study was to analyze the anatomotopographic location of the mandibular foramen in the right and left ramus, and to verify the influence of the amount of dental alveoli on the foramen position. Thirty-five adult dry human mandibles of Araraquara Dental School, UNESP - São Paulo State University were assessed, with or without dental alveoli. Measurements were obtained, using a ruler and a digital caliper. The following distances were measured: Fl - distance between the lowest point of the mandibular incisure and the mandibular foramen (F point); FB - distance between the mandibular base and F point; FP - distance between the posterior margin of the ramus and F point; FA - distance between the anterior margin of the ramus and F point; FT - distance between the apex of the retromolar trigone and F point. The Mann-Whitney test was used to compare each measurement according to hemi-arch, and the Kruskal-Wallis test was used to analyze the influence of the presence of alveoli on the measures. For multiple comparison, Dunn's method was used. There was no statistically significant difference in the location of the mandibular foramen when compared to the right and left hemi-arches. The amount of dental alveoli influenced, significantly, only on FA and FP distances. Thus, it was concluded that the right and left mandibular ramus showed symmetry in the location of the mandibular foramen, and the amount of alveoli influenced on the distances of the anterior and posterior margins of the mandibular rams, in relation to the mandibular foramen.

El objetivo de este trabajo fue evaluar la posición anátomo-topográfica del foramen mandibular en ambas ramas de la mandíbula y verificar la influencia de la cantidad de alvéolos dentales en la posición del foramen. Se evaluaron 35 mandíbulas humanas secas de individuos adultos de la Facultad de Odontología de Araraquara, Universidade Estadual Paulista - UNESP, con o sin alvéolos dentales. Se utilizó regla y calibrador digital para realizar las mediciones de las distancias entre: el punto más profundo de la incisura de la mandíbula y el foramen mandibular (FI); base de la mandíbula y el foramen (FB); margen posterior de la rama mandibular y el foramen mandibular (FP); margen anterior de la rama mandibular y el foramen (FA) y la distancia entre el vértice del trígono retromolar y el foramen mandibular (FT). Para la comparación de cada medida según hemiarcada se realizó el test de Mann-Whitney y para la influencia de la presencia de alvéolos en las medidas se utilizó el test de Kruskal-Wallis y para comparación múltiple el método de Dunn. No hubo diferencia estadística significativa en la localización del foramen mandibular al comparar el hemiarco mandibular derecho con el izquierdo. La cantidad de alvéolos dentales interfirió, de manera significativa, sólo en las distancias FA y FP. Se concluyó que las ramas mandibulares derecha e izquierda presentan simetría en el posicionamiento del foramen mandibular y la cantidad de alvéolos interfirió en las distancias de las márgenes anterior y posterior de la rama mandibular en relación con el foramen de la mandíbula.
Localización del foramen mandibular según la cantidad de los alvéolos dentales
Keywords: Anatomy; Mandibular foramen; Mandibular anatomy